2019
DOI: 10.1128/mbio.01332-19
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection Promotes Epithelial Cell Growth by Attenuating Differentiation-Dependent Exit from the Cell Cycle

Abstract: Epstein-Barr virus (EBV) is a human herpesvirus that is associated with lymphomas as well as nasopharyngeal and gastric carcinomas. Although carcinomas account for almost 90% of EBV-associated cancers, progress in examining EBV’s role in their pathogenesis has been limited by difficulty in establishing latent infection in nontransformed epithelial cells. Recently, EBV infection of human telomerase reverse transcriptase (hTERT)-immortalized normal oral keratinocytes (NOKs) has emerged as a model that recapitula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 47 publications
4
39
0
Order By: Relevance
“…EMT contributes to cancer progression and metastasis by inducing migration, invasion, and inhibition of cell adhesion [27]. In the present study, EBV infection induced mesenchymal phenotypes, migration, and invasion of infected cells (Figures 6 and 7).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…EMT contributes to cancer progression and metastasis by inducing migration, invasion, and inhibition of cell adhesion [27]. In the present study, EBV infection induced mesenchymal phenotypes, migration, and invasion of infected cells (Figures 6 and 7).…”
Section: Discussionsupporting
confidence: 57%
“…There are many reports that EBV is involved in the development of oropharyngeal cancer. An immortalized keratinocyte-based model has been shown to be susceptible to EBV [26,27]. Here we show for the first time that EBV establishes a latent infection in two squamous epithelial cells, which were well differentiated HSC1 cells and poorly differentiated SCC25 cells.…”
Section: Discussionmentioning
confidence: 66%
“…Lymphoblastoid cell lines (LCL) represent a good tool to study the formation of EBV-associated lymphomas. However, EBV infection to primary epithelial cells induces lytic infection [ 63 , 64 ], therefore primary epithelial cells are not suitable for oncogenic study. Instead, cell lines originated from cancers are used, because these cell lines often show latent infection of EBV.…”
Section: Ebv and Npc Carcinogenesismentioning
confidence: 99%
“…EBV has been linked to the development of epithelial cancers such as nasopharyngeal carcinoma and gastric cancer [ 39 , 52 ]. Even though EBV infection in epithelial cells is generally lytic, it has been observed that a latency state can be established in cells that show prior genomic DNA damage, like cyclin D1 overexpression [ 53 , 54 , 55 ].…”
Section: Epstein–barr Virus In Oral Cancermentioning
confidence: 99%